(untitled) (Global Journal of Medical Research, 2021)
Therapy by Monoclonal antibodies is considered extremely hoping method for cancer therapy. But cancer cells have variable methods for resistance by multiple genetic mutations. The aim of that article to illustrate tagging monoclonal antibodies by gallium containing solamargine glycoside within the antibody by glycosylation the asparagine of its Fc portion. Malignant cells need to a big extent high carbohydrate content for aerobic glycolysis for cancer progression. Solamargine as a specific glycoside can be diffused easily and effectively into malignant cells with a high degree of specificity. Complexion gallium to solamargine then conjugation into monoclonal antibodies will increase Monoclonal antibody potency and affinity by Warburg effect based mechanism and gallium particles. Gallium can be retained for a long time inside malignant cells. By that method, the monoclonal antibody will be targeted to cancer cells by solamargine, retained gallium particles besides its functioning specific Fab region.